Evaluation of Collagen Birefringence in Oral Reactive Lesions Using Picrosirius Red Stain Under Polarized Light Microscopy: An Observational Microscopic Study - A. P. Shirona; Usha Hegde; H. S. Sreeshyla (Wolters Kluwer Medknow Publications, 2021)
Introduction: Oral reactive lesions are relatively common. Collagen is the basic component of such overgrowths that could be fibrous or inflammatory. Hence, understanding the type, nature, and distribution of collagen fibers can aid in our knowledge and better management of these lesions. Materials and Methods: Ten paraffin blocks of each of the following lesions − giant-cell granuloma (L1), inflammatory fibrous hyperplasia (L2), pyogenic granuloma (L3), fibroma (L4), and peripheral ossifying fibroma (L5) − were retrieved from the archives. They were analyzed for their collagen birefringence property under polarized microscopy after picrosirius red stain. The demographic details of all the cases were recorded and evaluated. Results: In our study, giant-cell granulomas were commonly observed between third and seventh decades of life, inflammatory fibrous hyperplasias between second and fifth decades of life, yogenic granulomas in sixth decade, fibromas in fifth and sixth decades, and peripheral ossifying fibromas in second and fourth decade of life. All the lesions were predominant in females and commonly observed on gingiva. L5 lesions showed more areas of green birefringence followed by L1, L2, and L3 groups of lesions showed more of red birefringence than other lesions. Mixed birefringence of orange-red and green-yellow was almost same in all the lesions. All these findings were significant statistically. Conclusion: A plausible conclusion that the lesions with mature red fibers have better prognosis than the lesions with immature green fibers, in reactive oral lesions could be drawn.